CXCR7 in cardiomyocytes prevents cardiac dysfunction after myocardial infarction. (25th November 2020) - Ishizuka, M; Harada, M; Toko, H; Zhao, C; Guo, J; Bujo, S; Yanagisawa-Murakami, H; Komuro, I
Abstract: Background: Beta blockers and angiotensin II receptor blockers take effect through G protein-coupled receptors (GPCRs) and their protective roles in heart failure are partially attributable to beta-arrestin biased agonism. CXCR7, a chemokine receptor, is beta-arrestin biased receptor and one of the most expressing GPCRs in the heart. CXCL12 is a common ligand of CXCR4 and CXCR7 and is known to ameliorate myocardial infarction (MI), reportedly through CXCR4 dependent mechanisms. However, the role of another receptor, CXCR7 and its downstream target including beta-arrestin is not fully elucidated in MI. Purpose: The aim of this study is to uncover the role of CXCR7 in cardiomyocytes after MI. Methods: First, we quantified CXCR7 mRNA expressions in neonate rat cardiomyocytes (NRCM) in a dish by qRT-PCR. NRCMs were treated with CXCR7 agonist: TC14012 and phosphorylation of extracellular signal regulated kinase (ERK) was measured as readout of the downstream of CXCR7, with immunoblotting. Second, MI was induced by left anterior descending artery (LAD) ligation in male 12-week-old mice. We explored spatial expressions of CXCR7 by qRT-PCR in infarct, peri-infarct and remote zones of wild-type MI mice. Finally, we developed cardiomyocyte-specific CXCR7 knockout mice (cKO) by the Cre/loxP system and analyzed CXCR7 expression in cKO by qRT-PCR. LAD ligation was also performed in cKO and littermate controls (Ctl). Heart weight (HW) was measured and systolic function was examined by echocardiography 4 weeks after ligation. Phosphorylated ERK was evaluated with immunoblotting one-day after ligation. Results: First, we found that CXCR7 expression was significantly higher in NRCM than neonatal rat fibroblasts (NRFB) and ERK was phosphorylated by CXCR7 stimulation in NRCM. Second, CXCR7 expression was higher in infarct and peri-infarct zones than remote zones. Finally, cardiomyocyte-specific knockout of CXCR7 resulted in 78±21% reduction of CXCR7 expression in the whole heart. HW and left ventricular area was significantly greater (HW: Ctl 190.7±18.4, cKO 220.3±26.4 mg) and fractional area change of left ventricle was significantly lower in cKO than those in Ctl 4 weeks after MI (LV FAC: Ctl 20.6±4.9%, cKO 13.9±5.4%), indicating that loss of CXCR7 in cardiomyocytes caused left ventricle enlargement and systolic dysfunction. One day after MI of Ctl heart, ERK was more phosphorylated in peri-infarct zone than remote zone. However, this ERK phosphorylation in peri-infarct zone was reduced in cKO MI heart. Conclusion: We revealed that CXCR7 is expressed in cardiomyocytes and deletion of this chemokine receptor in cardiomyocytes resulted in ventricle enlargement and systolic dysfunction possibly through ERK phosphorylation in peri-infarct zone. Therefore, CXCR7 in cardiomyocytes could prevent cardiac dysfunction after myocardial infarction, which may be another pathway of CXCL12 dependent-protective effect. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI